Transthoracic echocardiography as a diagnostic tool in the identification of saddle pulmonary thromboembolism - Sunanda, Pasupuleti; Saiteja, Kodamanchili (International Journal of Advances in Medicine, 2025)
Pulmonary thromboembolism (PTE) is a common and potentially fatal emergency that results from thrombi mostly originating from deep veins of lower limbs. It is the third most frequent cause of death after myocardial infarction and stroke, with wide clinical spectrum ranging from asymptomatic emboli to sudden death. A particularly severe variant is saddling pulmonary embolism, defined by large thrombus lodges at bifurcation of main pulmonary trunk. Computed tomography pulmonary angiography (CTPA) remains the gold standard for diagnosing PTE. However, its use may be limited by hemodynamic instability, contrast allergies, renal impairment, or unavailability in resource-limited settings. In such scenarios a reliable bedside diagnostic alternative becomes essential. Given the urgency of diagnosis in saddle PTE and limitations of CTPA in critical care settings, echocardiography may serve as an important adjunct in early detection and triage.